Pojok Baca Kelas dalam Meningkatkan Budaya Literasi Siswa dalam Program Kampus Mengajar 7 di SD Negeri Jerukwangi di Kandangan, Kabupaten Kediri - Fediansah, Teddy Candra; Surindra, Bayu (JPEAKU (Jurnal Pendidikan Ekonomi Akuntansi Kewirausahaan), 2025)
Reading is important in the teaching and learning process. Reading is the process of absorbing knowledge through reading or writing. Literacy is a basic ability that must be mastered in processing and searching for information. To improve students' literacy culture, one of them can be done by creating a class literacy corner. Based on the results of observations at Jerukwangi Elementary School, it is known that the library in the school is in a state of being renovated by Kampus Mengajar students so that literacy culture activities, especially in the school library, automatically stop. Therefore, to overcome this problem, through the Kampus Mengajar program, a class literacy corner was created which is expected to improve students' literacy culture with all the existing obstacles. Using a qualitative descriptive method with data collection techniques in the form of observation and documentation. The implementation of community service activities is carried out by applying a class reading corner. The results of this community service activity can instill in students to create and improve a reading culture and habits of various things related to reading.